The Potential of Waste-Based Renewable Energy with A Gas Landfill System in Palopo - Nur, Muh. Syainal; Husen, Achmad; Purwandari, Dian Alfia (Eduvest - Journal of Universal Studies, 2023)
The government encourages the development of waste management by utilizing waste as a new renewable energy source through waste to energy technology as an effort to overcome the increasing volume of waste and the dependence of electricity production from new coal mineral resources. This study aims to explain how much waste-based renewable energy potential in Palopo can produce through landfill gas. The research method uses the LandGem-v302 tool to calculate landfill gas production, calculate the economic feasibility value using the investment criteria net present value, internal rate of return, benefit cost ratio and payback period. The results of the LandGem-v302 test with projected data for 2024-2030 show that the volume of waste at the Mancani landfill has the potential to produce landfill gas and methane gas to produce renewable energy for approximately 80 years of production from 2025-2110. The economic value feasibility test also shows that the economic value of waste based EBT can be categorized as feasible. Thus, the projection of waste in Palopo City in 2024-2030 has the potential to produce renewable energy and is worth investing in for long-term development in Palopo.